Bbc3 Loss Enhances Survival and Protein Clearance in Neurons Exposed to the Organophosphate Pesticide Chlorpyrifos. (21st July 2021) - Anderson, Faith L; von Herrmann, Katharine M; Young, Alison L; Havrda, Matthew C
Abstract: Exposure to environmental toxicants can increase the risk of developing age-related neurodegenerative disorders. Exposure to the widely used organophosphate pesticide chlorpyrifos (CPF) is associated with increased risk of developing Alzheimer's disease and Parkinson's disease, but the cellular mechanisms underlying CPF toxicity in neurons are not completely understood. We evaluated CPF toxicity in mouse primary cortical neuronal cultures, using RNA-sequencing to identify cellular pathways modulated by CPF. CPF exposure altered the expression of genes associated with intrinsic apoptosis, significantly elevating expression of the pro-apoptotic mediator Bbc3/Puma . Bbc3 loss attenuated CPF driven neurotoxicity, induction of other intrinsic apoptosis regulatory genes including Trp53 and Pmaip1 (encoding the NOXA protein), and cleavage of apoptosis executors caspase 3 and poly (ADP-ribose) polymerase (PARP). CPF exposure was associated with enhanced expression of endoplasmic reticulum stress-related genes and proteins and the accumulation of high molecular weight protein species in primary neuronal cultures. No evidence of alterations in the ubiquitin-proteosome system were observed, however, autophagy-related proteins were upregulated in CPF-treated Bbc3 −/− neuronal cultures compared with identically exposed WT cultures. Elevated autophagy-related protein expression in Bbc3 −/− neuronal cultures was associated with a reduction in CPF-induced high molecular weight alpha-synuclein and tau immunoreactive protein aggregates. Studies indicate that Bbc3 −/− neuronal cultures enhance the endoplasmic reticulum stress response and upregulate protein clearance mechanisms as a component of resistance to CPF-mediated toxicity.